The Effectiveness of Using Audio Visual Media in Improving Students' Ability to Understand the Court Process (Case Study on Judicial Practice Course) - Takdir, Takdir; Rahmawati, Rahmawati; Nur, Muh. Tahmid (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the effectiveness of using an audio-visual-based online trial practice module, the factors and efforts to improve students' understanding of the practical trial materials. This research is a quantitative research with descriptive statistical method. Data collection techniques used in this study consisted of observation and questionnaires. Respondents in this study amounted to 98 people. The data analysis used in this research is using descriptive statistical data analysis. The results showed that in the initial test, students' understanding of the practical trial material was 122.37, while when using the online trial practice module the average level of student understanding was 137.39. Therefore, if we compare from the initial test to the post test, there is an increase of 23.02. This shows that the use of the online trial practice module is effective in increasing the understanding of law students at the Sharia Faculty of IAIN Palopo. The inhibiting factors in using the online trial module are network constraints, direct trial review constraints and trial mastery techniques. While the supporting factors are easily accessible material, complete and current material and interesting online material. Efforts to increase student understanding through the use of online court practice modules can be carried out through the use of videos of national legal experts, easy downloadable access to literature, the addition of video practice trials in various cases, the provision of trial practice game features and the provision of commentary features on the online module.